Anthropocosmic Theatre Theatre, Ritual, Consciousness - Núñez, Nicolás (University of Huddersfield Press, 2019)
This new edition of Núñez's Anthropocosmic Theatre contains the text of the original English translation plus additional contributions from Núñez and others. In part one, Núñez traces his researches in Nahuatlan, Tibetan and western theatre, to arrive at his design for a theatre of the human in the cosmos. Part Two explores how this work has developed, during the last three decades, into an approach to performance training and production that uniquely combines ritual and contemplative influences. New and previously untranslated writing from Núñez presents his idiosyncratic view of an awakened and expansive role for theatre today.